Mycoplasma spp. mastitis — approach to diagnosis. (2nd July 2020) - Manning, Al
Abstract : Mycoplasma spp. mastitis outbreaks are rare, but when they occur they tend to be characterised by recurrent mastitis that is non-responsive to treatment, and a high rate of subclinical infections. These symptoms are often seen in conjunction with chronic calf pneumonia, and polyarthritis. General screening of individual cows or bulk tanks for Mycoplasma spp. is likely to result in more false positives than true positives, whichever test is chosen. Instead of using screening tests, veterinary surgeons should use targeted investigations on farms that meet the criteria of a suspected Mycoplasma spp. outbreak. For investigating individual animals, the most accurate test is likely to be bacteriological culture using selective growth media. For investigating bulk tanks, Mycoplasma bov is antibody testing is most sensitive but should be complemented with polymerase chain reaction (PCR) or culture to detect other species. Diagnostic sensitivity is increased by repeating or using a combination of tests, however this will increase the risk of false positives.